Effect of tranexamic acid on markers of inflammation in children undergoing craniofacial surgery. Issue 1 (29th September 2020) - Fenger‐Eriksen, Christian; Rasmussen, Mads; Juul, Niels; Krog, Jan; Hvas, Anne‐Mette
Abstract: Background: Tranexamic acid (TXA) reduces blood loss and transfusion requirements during craniosynostosis surgery in small children. Possible interaction from TXA on the inflammatory system is unknown. Objective: To evaluate the effect of TXA on a wide range of inflammatory markers in children receiving TXA in a randomized, blinded, and placebo controlled study design. Methods: Thirty children undergoing craniosynostosis surgery with significant blood loss received TXA (bolus dose of 10 mg kg −1 followed by 8 hours continuous infusion of 3 mg kg −1 h −1 ) or placebo in a randomized, double‐blinded study design. Using a new proximity extension assays employing a panel of inflammatory biomarkers samples was used for analysis of blood samples obtained pre‐operatively, 4 and 24 hours after operation. Results: Ninety‐two inflammatory parameters were measured. TXA did not affect any of the measured parameters as compared with placebo. Among 34 of the 92 pro‐ and antiinflammatory parameters investigated changes were observed between pre‐operative, 4 or 24 hours, respectively, reflecting immune activation during surgical stress. Conclusion: TXA administration in a low‐dose regimen including bolus followed by 8 hours infusion during craniosynostosis surgery did not change any of 92 inflammatory markers as compared with placebo.